Development and Evaluation of Ondansetron Orally Disintegrating Tablets - Bipin Pustake; Vikram Gharge; Ratnakar Korhale; Anil Gadhe (University of Huddersfield Press, 2019)
Orally disintegrating tablet (ODT) has number of advantages like faster onset of action, ease of administration, rapid disintegration and dissolution etc. A novel attempt has been made to develop orally disintegrating tablets of Ondansetron by using two approaches, one is soluble hydrophilic matrix by superdisintegrant and other is effect of sweetener on the formulation. Direct compression method was employed for making orally disintegrating tablets. The formulated orally disintegrating tablets have rapid disintegration property for better patient compliance. Formulated tablets were evaluated for physical parameters along with wetting time, disintegration time, drug content and "in vitro" dissolution. In first approach it was found that batch F7 containing Crospovidone (Polyplasdone XL 10) 10 mg showed minimum disintegration time (i.e. approx. 7.00 seconds) with maximum drug release. Wetting time for batch F7 was found to be minimum (i.e. 12 seconds). In second approach of selection of sweetener batch F 10 containing Sodium saccharin was found better in terms of Impurity study (Relative Substances study).Impurity was found within the specified limit compared to other two sweeteners. Stability study was carried out on optimized formulation. Overall batch containing 10 mg Crospovidone (Polyplasdone XL 10) along with Sodium Saccharin was found stable both physically and chemically.